Comparison of choroidal thickness and lens thickness among subtypes of angle-closure disease - Sai Lakshmi Suvarna Yeluguri; Mithun Thulasidas; Ajita Sasidharan; V. Rajesh Prabu; M. Prabhu Shanker (The Pan-American Journal of Ophthalmology)
Purpose: The purpose of the study was to evaluate choroidal thickness and lens thickness among various subtypes of angle-closure disease and compare it with healthy controls. Methods: This observational comparative study was conducted between June 2023 and February 2024 at our eye hospital, including eyes with subtypes of angle-closure disease and healthy controls. Lens thickness was measured using an automated optical biometer, and choroidal thickness was measured using enhanced depth imaging spectral-domain optical coherence tomography in the subtypes of angle-closure disease and healthy control subjects. Results: One hundred and twenty-four eyes were enrolled, including 93 angle-closure disease eyes and 31 healthy eyes. The mean choroidal thickness was significantly higher in angle-closure subtypes than healthy controls (247.19 ± 40.97 μm, 318.81 ± 24.81 μm, 383.81 ± 53.06 μm, and 173.65 ± 28.19 μm in primary angle-closure [PAC] suspect, PAC, PAC glaucoma, and healthy controls, respectively [P < 0.001]). The mean lens thickness was higher in angle-closure disease compared to the control group (P < 0.01). Conclusion: Increased choroidal thickness might be another anatomic characteristic of PAC eyes along with increased lens thickness. This finding may support the hypothesis that choroidal enlargement plays a part in the development of PAC disease.